Biospecimens and molecular and cellular biomarkers in aneurysmal subarachnoid hemorrhage studies: common data elements and standard reporting recommendations - Chou, Sherry; Macdonald, R. Loch; Keller, Emanuela; Etminan, Nima; Hackenberg, Katharina (Neurocritical care, 2019)
Development of clinical biomarkers to guide therapy is an important unmet need in aneurysmal subarachnoid hemorrhage (SAH). A wide spectrum of plausible biomarkers has been reported for SAH, but none have been validated due to significant variabilities in study design, methodology, laboratory techniques, and outcome endpoints.MethodsA systematic review of SAH biomarkers was performed per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The panel’s recommendations focused on harmonization of (1) target cellular and molecular biomarkers for future investigation in SAH, (2) standardization of best-practice procedures in biospecimen and biomarker studies, and (3) experimental method reporting requirements to facilitate meta-analyses and future validation of putative biomarkers.ResultsNo cellular or molecular biomarker has been validated for inclusion as “core” recommendation. Fifty-four studies met inclusion criteria and generated 33 supplemental and emerging biomarker targets. Core recommendations include best-practice protocols for biospecimen collection and handling as well as standardized reporting guidelines to capture the heterogeneity and variabilities in experimental methodologies and biomarker analyses platforms.ConclusionSignificant variabilities in study design, methodology, laboratory techniques, and outcome endpoints exist in SAH biomarker studies and present significant barriers toward validation and translation of putative biomarkers to clinical use. Adaptation of common data elements, recommended biospecimen protocols, and reporting guidelines will reduce heterogeneity and facilitate future meta-analyses and development of validated clinical biomarkers in SAH.